Pengembangan Kompetensi Digital Sebagai Upaya Peningkatan SDM Posyandu di Beji Timur, Depok, Jawa Barat - Viving Frendiana; Budi Utami; Zulhelman; Agus Wagyana; Mohamad Fathurahman; Shita Herfiah (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2024)
This community service aims to improve the digital competence of regional administrators in Beji Timur Village, Depok City, through Microsoft Office and Google Apps training. The background of this activity is the need of residents, especially for pos pelayanan terpadu (posyandu, or integrated health service post) cadres, to improve their skills in using the software to support administrative tasks. The training was conducted face-to-face, with a demonstration approach and direct practice accompanied by lecturers and students from the Politeknik Negeri Jakarta (Jakarta State Polytechnic). The evaluation of the activity included a pretest, posttest, and participant satisfaction questionnaire, which showed a significant increase in participant abilities and a positive response to the experience and benefits of the training. The results of this activity showed that this training was effective in improving the digital competence of participants, with an average score of 4.5 for training benefits, 4.8 for training experience, and 4.9 for interest in participating in similar training in the future. This activity is expected to have a long-term impact on improving the quality of human resources in Beji Timur Village. Keywords: digital competence, training, Microsoft Office, Google Apps, community servicePengabdian masyarakat ini bertujuan untuk meningkatkan kompetensi digital pengurus wilayah di Kelurahan Beji Timur, Kota Depok, melalui pelatihan Microsoft Office dan Google Apps. Latar belakang kegiatan ini adalah kebutuhan warga, terutama kader pos pelayanan terpadu (posyandu), untuk meningkatkan keterampilan mereka dalam menggunakan perangkat lunak guna mendukung tugas administratif. Pelatihan dilakukan secara tatap muka, dengan pendekatan demonstrasi dan praktik langsung yang didampingi oleh dosen dan mahasiswa dari Politeknik Negeri Jakarta. Evaluasi kegiatan meliputi pretest, posttest, dan angket kepuasan peserta, yang menunjukkan peningkatan signifikan pada kemampuan peserta serta respons positif terhadap pengalaman dan manfaat pelatihan. Hasil dari kegiatan ini menunjukkan bahwa pelatihan ini efektif dalam meningkatkan kompetensi digital peserta, dengan skor ratarata 4,5 untuk manfaat pelatihan, 4,8 untuk pengalaman pelatihan, dan4,9 untuk minat mengikuti pelatihan serupa di masa depan. Kegiatan ini diharapkan dapat memberikan dampak jangka panjang pada peningkatan kualitas SDM di Kelurahan Beji Timur. Kata kunci: kompetensi digital, pelatihan, Microsoft Office, Google Apps, pengabdian masyarakat